9-17x-5-4x=7

Simple and best practice solution for 9-17x-5-4x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-17x-5-4x=7 equation:


Simplifying
9 + -17x + -5 + -4x = 7

Reorder the terms:
9 + -5 + -17x + -4x = 7

Combine like terms: 9 + -5 = 4
4 + -17x + -4x = 7

Combine like terms: -17x + -4x = -21x
4 + -21x = 7

Solving
4 + -21x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -21x = 7 + -4

Combine like terms: 4 + -4 = 0
0 + -21x = 7 + -4
-21x = 7 + -4

Combine like terms: 7 + -4 = 3
-21x = 3

Divide each side by '-21'.
x = -0.1428571429

Simplifying
x = -0.1428571429

See similar equations:

| -x-8+14x=34 | | 3x+1y=21 | | 4-0.9k=4 | | 1x+2y=12 | | 3n^2-8n+5= | | -4(5+7y)+6(2y-9)= | | 33x^2-79x+40=0 | | -4(8-9x)= | | 49x^2-21x+2=0 | | X+3y-4=0 | | -4x+6y=-2 | | 3x+x=40 | | -9(5-3x)=9 | | 8(3n+7)-10n= | | 4k+-14+3k=21 | | 67x+45=67 | | -6(3y+5)= | | 6x+0.6=7x | | 2(v-5)=-(3v+5) | | (4*x)-6=(x*2)+4 | | 5m+7m=-4m | | 5(4n-3)= | | x+6=x*4 | | 6.2x-3+4x-1.2= | | y=-2(-1-1)(-1+3) | | 7(x-4)= | | 2x-y=16 | | 3x+7-2x= | | 3(a+2)-8=5-2(a-4) | | X=24+4x | | 8+2z=24 | | 5x-10=3x-2 |

Equations solver categories